A routine perspective on implementing reflective career conversations in education. Issue 2 (15th March 2017) - den Boer, Peter; Hoeve, Aimée
ABSTRACT: Reflective career conversations are a necessary instrument in the career guidance of students in vocational education. These conversations help students to learn from their (work) experiences and gain a better understanding of their motives on the labour market. Research shows that in a society in which change seems to become the only constant factor, knowing one's own motives in work is important. However, the introduction and implementation of reflective career conversations in Dutch vocational education is problematic. In this article, we introduce the concept of 'routines' to better understand the nature of these problems. The concept 'routine' allows us to understand in much more detail what is required to induce the necessary behavioural changes that are required from teachers, students and management. Recognition of the complexity of this process and the willingness to invest are necessary prerequisites to prevent reflective career conversations from becoming the next 'trick' or 'trendy innovation'.